Beyond decolonizing: global intellectual history and reconstruction of a comparative method. (3rd September 2021) - Herbjørnsrud, Dag
ABSTRACT: This article proposes to use the three terms complexity, connection, and comparison as part of a possible method for the discipline of global intellectual history. Taking the 1993 presidential address by anthropologist Anette Weiner as its starting point, the paper argues that the discipline of history of ideas is facing a challenge similar to that confronted by social anthropology a quarter of a century ago: It needs to reject the constrictions of 'cultural boundaries' and demonstrate 'a commitment to a global comparative perspective' instead. A global intellectual history of this nature would also be consistent with Arthur B. Lovejoy's statement that 'ideas are the most migratory things in the world'. The text proposes a method for global intellectual history based on the three aforementioned terms – exemplified by cases from Asia, Africa, Europe, and America. Scholars within several disciplines are increasingly arguing for the Academy to 'decolonize' and to offer a less ethnocentric narrative. By proposing a methodological draft for a global intellectual history, this paper argues that we can move beyond deconstruction and decolonization and focus instead on 'reconstruction' of a global and comparative perspective as a fruitful way forward for the discipline in the twenty-first century.